Rickettsial Infections among the Undifferentiated Febrile Patients Attending a Tertiary Care Teaching Hospital of Northern India: A Longitudinal Study - Mansoor, Tabeen (Infect Chemother, 2021)
BACKGROUND: Acute undifferentiated febrile illness (AUFI) is one of the most daunting challenges a physician faces in such settings. Among AUFI, rickettsial infections are most common and related infections (such as anaplasmosis, ehrlichiosis, and Q fever) which are caused by an unusual type of bacteria that can live only inside the cells of another organism. The present study was therefore planned with an objective to estimate the prevalence of rickettsial infection among patients of undifferentiated fever and to determine any association of socio-demographic characteristics with rickettsial disease. MATERIALS AND METHODS: Patients presenting with febrile illness and admitted or attending out-patient department of Sher-i-Kashmir Institute of Medical Sciences, Srinagar was approached and recruited in the study. Weil Felix Assay, enzyme-linked immunosorbent assay and indirect immunofluorescence assay were done to detect the anti-rickettsial antibodies. Serological evidence of a fourfold increase in IgG-specific antibody titer reactive with spotted fever group rickettsial antigen by indirect immunofluorescence antibody assays between paired serum specimens was considered a confirmatory diagnosis for the rickettsial disease. RESULTS: Most of the patients were males 61.6%, and most 46.2% were in the age group of 20 -39 years. Most of the patients, 80.8% belonged to rural areas, and 48% belonged to the upper middle (II) class of the socio-economic class according to modified Kuppuswamy scale. Of the studied participants, a majority, 47.0%, were determined undiagnosed, while 15.4% studied participants were diagnosed to have a rickettsial disease. In patients positive for typhus group, 67.8% were IgM positive, 28.5% were IgG positive, and only 3% were positive for IgM and IgG. In patients positive for Scrub Typhus Group, 32.7% were positive for IgM, and 62.0% were positive for IgG, and only 5.0% were positive for both IgM and IgG. In patients positive for spotted fever group, 36.1% were positive for IgM, and 58.5% were positive for IgG, and only 5.5% were positive for both IgM and IgG. The prevalence of rickettsial disease was found to be 11.3%. CONCLUSION: Rickettsial diseases, typhoid and brucellosis, were the most prevalent diseased diagnosed among patients reporting to hospitals with undifferentiated febrile illness. Clinicians must consider rickettsial diseases as one of the differential diagnosis while treating patients with fever.